Perpustakaan Nasional Republik Indonesia Sebagai Sumber Copy Cataloging - Wicaksono, Arief (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
Copy cataloging is a process to copy metada from one to other library catalogs. The study found that the sources for copy cataloging from the National library are online catalog, National Main Catalog (Katalog Induk Nasional), and Indonesian National Bibliography (Bibliografi Nasional Indonesia). For Indonesian National Bibliography, its copy cataloging has minimum download fiture in MARC and XML format. In order to be used widely, the National Library have promoted and conducted short workshops on copy cataloging along with e-library function. The study also found that there were libraries that have used its national library fiture into their libraries. However, as a general case in Indonesian libraries, copy cataloging, in which it has advantages, still remains lack of use for many libraries.